2009
DOI: 10.1177/0042085908322705
|View full text |Cite
|
Sign up to set email alerts
|

Different Folks, Different Hopes

Abstract: The educational aspirations of Black males in urban, suburban, and rural high schools were examined in this study, using a nationally-representative sample of respondents to the National Educational Longitudinal Study (NELS:88/00). Hierarchical linear regression analysis revealed statistically significant relationships between aspirations and SES, academic achievement, and urban city with high-SES, high-achieving, suburban Black males reporting the highest aspirations. Leveled and/or lower aspirations were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(14 citation statements)
references
References 49 publications
2
11
0
1
Order By: Relevance
“…Ismail et al (2019), assessing the role of SES in predicting reading comprehension by Malaysian university students, hypothesised that SES predicts reading comprehension of English as a second language (ESL) learner. Because SES influenced the cognitive development of educators, especially children from higher SES, i.e., highly educated parents with better employment and financial capability, generally embodies superior knowledge, skills, habits, and personality that in turn produce better academic attainment (Kainuwa et al, 2017;Strayhorn, 2009;Zhao et al, 2017). In contrast, lower SES families could not afford books, nutritious foods and a congenial home environment for their children.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Ismail et al (2019), assessing the role of SES in predicting reading comprehension by Malaysian university students, hypothesised that SES predicts reading comprehension of English as a second language (ESL) learner. Because SES influenced the cognitive development of educators, especially children from higher SES, i.e., highly educated parents with better employment and financial capability, generally embodies superior knowledge, skills, habits, and personality that in turn produce better academic attainment (Kainuwa et al, 2017;Strayhorn, 2009;Zhao et al, 2017). In contrast, lower SES families could not afford books, nutritious foods and a congenial home environment for their children.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Thereby, their parents have more financial resources to mobilise for afterschool classes and other facilities to boost the academic excellence of children (Zhao et al, 2017). Nevertheless, students from high SES families have greater access to information and relevant opportunities, which in turn accelerate their chances of performing better in academic examinations (Strayhorn, 2009).…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Além dos fatores que afetam o desempenho dos estudantes, as disparidades de desempenho entre estudantes urbanos e rurais têm sido investigadas na literatura recente. Diversos estudos mostram que os alunos de escolas em áreas rurais têm os piores resultados educacionais (Roscigno, Tomaskovic-Devey & Crowley, 2006;Strayhorn, 2009;Ramos, Duque & Nieto, 2016). Conforme destacam Roscigno & Crowley (2001), o baixo desempenho desses estudantes está relacionado à falta de recursos das famílias rurais e itens educacionais domésticos, além das baixas expectativas quanto às oportunidades de trabalho no meio rural, por parte dos pais e dos professores em escolas rurais.…”
Section: Revisão De Literaturaunclassified
“…Differences in the resources available to schools in different geographical areas and their consequences for educational achievement have been at the core of this concern. Studies have repeatedly shown that students in rural areas perform worse than students in (sub)urban areas (Reeves, 2012; Reeves & Bylund, 2005; Roscigno & Crowley, 2001; Roscigno et al, 2006; Strayhorn, 2009). However, few attempts have been made at providing a systematic explanation for these geographical disparities (Roscigno & Crowley, 2001).…”
Section: Inequalities Of Placementioning
confidence: 99%
“…Research into the existence of rural–(sub)urban disparities in educational outcomes has so far almost entirely been restricted to U.S.-based studies (e.g., Reeves, 2012; Reeves & Bylund, 2005; Roscigno & Crowley, 2001; Roscigno, Tomaskovic-Devey, & Crowley, 2006; Strayhorn, 2009). These studies show that students who attend schools in rural areas perform worse than students at (sub)urban schools.…”
Section: Introductionmentioning
confidence: 99%